2020
DOI: 10.1002/tpg2.20002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection for lentil breeding: Empirical evidence

Abstract: Genomic selection (GS) is a marker-based selection initially suggested for livestock breeding and is being encouraged for crop breeding. Several statistical models are used to implement GS; however, none have been tested for use in lentil (Lens culinaris Medik.) breeding. This study was conducted to compare the accuracy of different GS models and prediction scenarios based on empirical data and to make recommendations for designing genomic selection strategies for lentil breeding. We evaluated nine single-trai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 68 publications
(113 reference statements)
0
34
0
Order By: Relevance
“…Effective genomic cross-predictions of Pythium breeding values between the RR panel and the ADP do not support that the observed tolerance is exotic, but rather indicate a general quantitative tolerance to root rots available in Andean germplasm. Predictions across populations have been reported to be poor in lentil (Haile et al, 2020) and other crops (Charmet et al, 2014;Crossa et al, 2014), hence, the effective allelic diversity between ADP and RR panel must be similar. Taken together, our data suggests a quantitative mode of resistance of the traits evaluated here combining favorable different alleles from several precursors, in line with reports on Fusarium resistance (Ongom et al, 2012;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Effective genomic cross-predictions of Pythium breeding values between the RR panel and the ADP do not support that the observed tolerance is exotic, but rather indicate a general quantitative tolerance to root rots available in Andean germplasm. Predictions across populations have been reported to be poor in lentil (Haile et al, 2020) and other crops (Charmet et al, 2014;Crossa et al, 2014), hence, the effective allelic diversity between ADP and RR panel must be similar. Taken together, our data suggests a quantitative mode of resistance of the traits evaluated here combining favorable different alleles from several precursors, in line with reports on Fusarium resistance (Ongom et al, 2012;Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The first two datasets we use for evaluation are published datasets of lentil ( Lens culinaris ) (21). The authors of this study examined GP performance within-population, across-populations, and across-environments using a variety of models.…”
Section: Methodsmentioning
confidence: 99%
“…The data used in the wheat and lentil experiments are available from the sources referenced by their authors (21, 22). The carinata data is available on request.…”
Section: Data Availabilitymentioning
confidence: 99%
“…For example, prediction accuracy of GEBV for grain yield was estimated to be 0.64 in soybean, indicating good potential of using GS for this low heritable trait in this crop (Jarquín et al, 2014). In lentil, different GS models and prediction scenarios have been evaluated for GS by including G × E interactions and multiple traits (Haile et al, 2020). In this study, GS was found useful to accelerate genetic gain within population and across environments (Haile et al, 2020).…”
Section: Future Ways For Genomics‐assisted Breedingmentioning
confidence: 99%